Evolution and development: engine-driven endodontic rotary nickel-titanium instruments - Yuhong Liang; Lin Yue (Nature Publishing Group, 2022)
Abstract Various engine-driven NiTi endodontic files have been indispensable and efficient tools in cleaning and shaping of root canals for practitioners. In this review, we introduce the relative terms and conceptions of NiTi file, including crystal phase composition, the design of the cutting part, types of separation. This review also analysis the main improvement and evolution of different generations of engine-driven nickel-titanium instruments in the past 20 years in the geometric design, manufacturing surface treatment such as electropolishing, thermal treatment, metallurgy. And the variety of motion modes of NiTi files to improve resistance to torsional failure were also discussed. Continuous advancements by the designers, provide better balance between shaping efficiency and resistance to of NiTi systems. In clinical practice an appropriate system should be selected based on the anatomy of the root canal, instrument characteristics, and operators' experience.